LABOR INFORMALITY IN COMPANIES IN THE MICROCENTER OF CIUDAD DEL ESTE - Inocencia González Rejala, Dominga; Roció Chaparro Ramírez, Lilian; Jazmín Medina Benítez, Mónica; Arnaldo Dávalos Giménez, Luís; Rosa Trinidad de Ferreira, Nidia (Revista Gênero e Interdisciplinaridade, 2023)
Labor informality in companies takes place in the downtown area of Ciudad del Este, based on the reality of some companies. The general objective is to analyze the factors that influence labor informality in companies, in which the descriptive research design is used; the approach is quantitative. Information collection is carried out through an online survey, the questionnaire is used as an instrument; The field study was carried out in 15 clothing stores in the downtown area of Ciudad del Este, the population under analysis was made up of 120 workers of both sexes; The results released from the surveys have allowed us to draw several conclusions and achieve the objectives proposed in the research. The results have shown the existing labor informality, where the satisfaction of its members is revealed to be partially optimistic; Taking into account the data we observe, there is a need to implement the following aspects within the stores, such as receiving good remuneration according to the functions and according to the salary established by law, reducing working hours or receiving payment when working overtime. for said hours worked, decent treatment, obtain medical insurance that supports safety and health, due recognition for the performance of workers and job stability, mainly carry out the inspection of the entity in charge of ensuring the safety of workers, these It would improve the level of commitment and identity within the company and the state of well-being in general, which would have a positive impact on productivity.